Komunikasi dan Identitas Budaya Populer pada Komunitas Korea Lovers Surabaya (Faculty of Communications Science, Dr. Soetomo University, 2018)
Trend can always change rapidly, both from the type of music and other fields, such as dress styles and so on. With the emergence of a new trend then the community with so easily affected and follow the tren that is famous today. Pop culture today is not only dominated by Western culture, but Asian countries also began to show the uniqueness of its own pop culture. Not only Japan, Korea is now beginning to show its strength as an exporter of pop culture through entertainment that is in line with the industry in Korea. The popularity of K-POP in Indonesia has caused many emerging fan communities. These communities often hold events called Korean Days. The number of events - Korean Days event, causing some communities that have sprung up in Indonesia. One of them is KLOSS or is often interpreted with Korean Lovers Community Surabaya. The KLOSS community is formed as a platform for those who love Korean culture. They are not limited to the entertainment world of South Korea, but also learn the language.Keywords: identity, Pop-Culture, Community Korean lover